With knowledge and innovation in new tourism venture - Radovanović, Vladimir; Rendulić, Gordana (Hotel and Tourism Management, 2017)
Tourism is a dynamic economic activity characterized by numerous, rapid and unpredictable changes. Today, changes along with their continuity do not only condition the economic life of one society, but they have also become the way of life of economic subjects in every developed economy. The field of change is the biggest challenge for the management of every business system which necessarily includes the tourism organizations that are looking for models of efficient organization and innovations as the best solution for efficient business. Bearing in mind the positive effects of tourism development, it is necessary to achieve a higher level of competitiveness of this activity in the Republic of Serbia. The aim of the paper is to point to the importance of innovations in tourism companies and, through the different ways of defining and classifying innovations in this field, to help understand the concept of knowledge management and the creation of new innovations.